Travel time to provider is associated with advanced stage at diagnosis among low income head and neck squamous cell carcinoma patients in North Carolina. (February 2019) - Farquhar, Douglas R.; Masood, Maheer M.; Lenze, Nicholas R.; McDaniel, Philip; Mazul, Angela; Sheth, Siddharth; Zanation, Adam M.; Hackman, Trevor G.; Weissler, Mark; Zevallos, Jose P.; Olshan, Andrew F.
Highlights: We examine whether travel time affects late presentation of cancer. Travel time among low-income patients was associated with T stage at presentation. Travel may be a barrier to early diagnosis of HNSCC for disadvantaged patients. Abstract: Objective: There is considerable variation in the travel required for a patient with head and neck squamous cell carcinoma (HNSCC) to receive a diagnosis. The impact of this travel on the late diagnosis of cancer remains unexamined, even though presenting stage is the strongest predictor of mortality. Our aim is to determine whether travel time affects HNSCC stage at diagnosis independently of other risk factors, and whether this association is affected by socioeconomic status. Materials and methods: Cases were obtained from the CHANCE database, a population-based case-control study in North Carolina (n = 808). The mean age was 59.6 and 72% were male. Stage at diagnosis was categorized as early (T1-T2) or advanced (T3-T4) T stage and the presence or absence of nodal metastasis. Multivariate logistic regression models were used to estimate odds ratios for stage-at-diagnosis based on travel time, after adjustment for variables including demographics, income, insurance status, alcohol, and tobacco use. Results: The adjusted odds ratio (OR) of advanced T-stage at diagnosis was 1.97 for each hour driven (95% CI 1.36–2.87). There was no association with nodal metastases. There was a significant interaction between travel time and income (p = 0.026) with a pattern of higher ORs for increased distance among lower income (<20, 000) patients compared to the ORs for higher income (>20, 000) patients. Discussion: Travel time was an independent contributor to advanced T stage at diagnosis among low income patients. This suggests travel burden may be a barrier to early diagnosis of HNSCC for impoverished patients.